New Directions in Archaeological Science (TA28) - Fairbairn, Andrew; O'Connor, Sue; Marwick, Ben (Terra Australis, 2009)
Archaeological Science meetings will have a personality of their own depending on the focus of the host archaeological fraternity itself. The 8th Australasian Archaeometry meeting follows this pattern but underlying the regional emphasis is the continuing concern for the processes of change in the landscape that simultaneously effect and illuminate the archaeological record. These are universal themes for any archaeological research with the increasing employment of science-based studies proving to be a key to understanding the place of humans as subjects and agents of change over time. This collection of refereed papers covers the thematic fields of geoarchaeology, archaeobotany, materials analysis and chronometry, with particular emphasis on the first two. The editors Andrew Fairbairn, Sue O'Connor and Ben Marwick outline the special value of these contributions in the introduction. The international nature of archaeological science will mean that the advances set out in these papers will find a receptive audience among many archaeologists elsewhere. There is no doubt that the story that Australasian archaeology has to tell has been copiously enriched by incorporating a widening net of advanced science-based studies. This has brought attention to the nature of the environment as a human artefact, a fact now more widely appreciated, and archaeology deals with these artefacts, among others, in this way in this publication.